Desain Meja dan Kursi Tutorial Laboratorium Desain Produk dan Inovasi Menggunakan Metode 12 Prinsip Ergonomi dan Pendekatan Antropometri - Sinaga, Helena Hotmauli; Siboro, Benedikta Anna Haulian; Marbun, Chrisdio Ebenezer (Jurnal Sistem Teknik Industri, 2021)
The laboratory has an important thing to in producing graduates who are ready to work. In the laboratory itself, of course, it requires supporting facilities so that the participants can carry out learning activities properly. This is the same as the activity of developing a Product Design and Innovation laboratory at the Institut Teknologi Del which requires supporting facilities for its users. The purpose of this research is to design ergonomic desk and chair tutorial facilities that meets to users requirement. The method this research uses 12 ergonomic principles to identify user needs and translate them into Ergonomic Function Deployment (EFD) to develop House of Quality(HOQ) and designed by an anthropometric approach. The results of this study are the design of the tutorial desk and chair facilities with the 5-95th percentile of student body to meet their design use.